FORMATION OF MEDICAL CULTURE IN THE ACTIVITIES OF INTERNAL AFFAIRS BODIES (Conferencea, 2024)
The formation of a medical culture among law enforcement officers is a complex and interconnected process between society, education, and the professional environment, which work in partnership with each other. Society, through its core values and attitudes toward medical services, shapes the attitude of officers to health and medical care. These social feelings determine the organization and priorities of medical services. Education plays an important role in shaping medical culture. It provides employees with the necessary knowledge about hygiene, disease prevention, and first aid. In this process, it forms not only professional skills, but also medical and ethical culture, determines the attitude of employees to their own health and medical resources in accordance with the requirements of society.